Left Ventricular Diastolic Dysfunction as Predictor of Unfavorable Prognosis After ESUS - Bielecka-Dabrowa, Agata (J Multidiscip Healthc, 2021)
OBJECTIVE: Identification of echocardiographic, hemodynamic and biochemical predictors of unfavorable prognosis after embolic strokes of undetermined etiology (ESUS) in patients at age <65. PATIENTS AND METHODS: Out of 520 ischemic stroke patients we selected 64 diagnosed with ESUS and additional 36 without stroke but with similar risk profile. All patients underwent echocardiography, non-invasive assessment of hemodynamic parameters using SphygmoCor tonometer and measurements of selected biomarkers. Follow-up time was 12 months. RESULTS: Nine percent of patients died, and recurrent ischemic stroke occurred in 9% of patients only in the ESUS group. Atrial fibrillation (AF) occurred in 10% of patients and the ESUS group had a significantly poorer outcome of AF in the first 2 months after hospitalization. The outcome of re-hospitalization was 28% in the ESUS group and 17% in the control group. In the multivariate analysis mean early diastolic (E’) mitral annular velocity (OR 0.75, 95% CI: 0.6–0.94; p=0.01) was significantly associated with cardiovascular hospitalizations. The only independent predictor of recurrent stroke was the ratio of peak velocity of early diastolic transmitral flow to peak velocity of early diastolic mitral annular motion (E/E’) (OR 0.75, 95% CI: 0.6–0.94; p=0.01). E/E’ was independently associated with composite endpoint (death, hospitalization and recurrent stroke) (OR 1.90, 95% CI 1.1–3.2, p=0.01). CONCLUSION: The indices of diastolic dysfunction are significantly associated with unfavorable prognosis after ESUS. There is a robust role for outpatient cardiac monitoring especially during the first 2 months after ESUS to detect potential AF.